Transmission channels of intergenerational income mobility: Empirical evidence from Germany and the Unites States - Mustafa Coban; Sarah Sauerhammer (Julius Maximilian University of Würzburg, Chair of Economic Order and Social Policy, 2017)
Relying on harmonized individual data for Germany and the United States, we perform a country comparison regarding the underlying mechanisms of the intergenerational income mobility. By applying descriptive and structural decomposition methods, we estimate the relative importance of the transmission of financial resources and endowments within a family. Although the results from both approaches are similar, the structural decompositions rather allow a causal interpretation due to instrumenting the transmission channels. Whereas a family's financial resources and endowments almost equally contribute to the intergenerational income mobility in Germany, endowments account for solely 30 percent in the United States. Nonlinearities in the transmission channels along the income distribution in the United States indicate that the endowment effect slightly decreases in relative importance across income percentiles. In Germany, there are no significant nonlinearities at all.
Keywords: I24; J24; J62; 330; intergenerational income elasticity; intergenerational mobility; financial resources; human capital